SIMILARITIES AND DIFFERENCES OF ACCUSATIVE CASE IN ENGLISH AND UZBEK LANGUAGES - Norpultova Nargiza Nuriddin qizi; Mehrigul Najmiddinova Najmiddin qizi (PEDAGOGS, 2024)
Annotation: The purpose of this article is to provide specific information regarding the use of accusative cases in Uzbek and English